2021
DOI: 10.1177/23259671211015239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Achilles Tendon Repair on Performance Outcomes After Return to Play in National Collegiate Athletic Association Division I Basketball Athletes

Abstract: Background: Achilles tendon (AT) ruptures are devastating injuries that are highly prevalent among athletes. Despite our understanding of the effect of AT rupture and in particular its relationship to basketball, no study has examined the effects of AT rupture and repair on performance metrics in collegiate basketball players. Purpose: To evaluate the effect of AT rupture and subsequent surgical repair on performance metrics in National Collegiate Athletic Association (NCAA) Division I basketball players who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…No study in our review collected data related to menstrual status of female participants despite several authors discussing that sex-specific hormone differences may be related to the difference in incidence of Achilles tendon rupture between male and female athletes reported as ranging from 5:1 to 6:1. 20,24,26 Bryant et al 5 found that long-term estrogen exposure reduced overall Achilles tendon strain and attritional wear likely because of its negative effect on collagen synthesis. This indicates a potential predisposition to Achilles injuries in aging females that fluctuates based on estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…No study in our review collected data related to menstrual status of female participants despite several authors discussing that sex-specific hormone differences may be related to the difference in incidence of Achilles tendon rupture between male and female athletes reported as ranging from 5:1 to 6:1. 20,24,26 Bryant et al 5 found that long-term estrogen exposure reduced overall Achilles tendon strain and attritional wear likely because of its negative effect on collagen synthesis. This indicates a potential predisposition to Achilles injuries in aging females that fluctuates based on estrogen levels.…”
Section: Discussionmentioning
confidence: 99%
“…ATR causes acute pain, decreased muscle strength, physical dysfunction and limitation of activities of daily living [43]. ATR can have detrimental effects on return to play, performance level, and career outcomes in elite athletes [1, 9, 14, 17, 21, 24, 36, 38, 41, 44]. The Achilles Tendon Total Rupture Score (ATRS) is the only patient‐reported outcome measure (PROM) specific to the evaluation of ATR outcomes.…”
Section: Introductionmentioning
confidence: 99%